Implementing Differentiated Instruction in Islamic Religious Education to Strengthen Religious Character in Primary Islamic Schools - Fachrul Rozi Sasikome; Mehammad Shaleh Gunung; Dina Mardiana (Journal of Teacher Training and Educational Research, 2026)
This study aims to describe the implementation of differentiated learning in Islamic Religious Education to strengthen students’ religious character at MI Muhammadiyah Tahuna. This research employed a qualitative approach with a case study method. Data were collected through interviews, classroom observations, and documentation involving Islamic Religious Education teachers, the head of the madrasah, and students. The data were analyzed through data condensation, data display, and conclusion drawing. The findings show that differentiated learning was implemented by adjusting learning activities to students’ readiness, abilities, interests, and learning needs. Teachers applied content, process, and product differentiation through varied activities such as discussion, worship simulation, collaborative learning, reflection, posters, Islamic poetry, and personal assignments. The implementation of differentiated learning contributed to strengthening students’ religious character, particularly in worship discipline, honesty, responsibility, confidence, respect for differences, and social awareness. Supporting factors included teacher commitment, institutional support, and student enthusiasm, while the constraints included limited facilities, large class size, limited learning time, and teachers’ difficulty in designing varied learning materials. This study concludes that differentiated learning in Islamic Religious Education can become an adaptive and meaningful pedagogical strategy for strengthening students’ religious character in primary Islamic education.